AN AYURVEDIC APPROACH IN THE MANAGEMENT OF NEUROCYSTICERCOSIS: A CASE STUDY - *Amit Nakanekar; Suraj Rathod; Rajni Gurmule; Ajit Devikar; J.D. Gulhane (International Journal of Ayurveda and Pharma Research, 2015)
Neurocysticercosis is form of cysticercosis. It is a infection of the brain by the larval form of the pork tapeworm taenia solium. In 80% cases symptoms are seizures, visual disturbance, nausea, abdominal cramps, and diarrhoea. Among the rare incidences some abnormal symptoms occur are dysarthria, extra ocular movement palsy, hemiplegia, movement disorder, gait disturbance.A 49 year old male patient came to OPD of GAC Nagpur with complaints of weakness in left side of upper and lower limb, slurred speech, focal convulsion of left hand, difficulty in walking since 10 days and having H/O seizures 30 year ago. Patient was diagnosed as a case of Neurocysticercosis through CT brain, CSF, and other haematological investigations. Patient was admitted and treated with Ayurvedic principle of Krimi and Vatavyadhi management. Patient showed complete recovery in clinical assessments in terms of speech, gait weakness.